2017
DOI: 10.1177/0269215516687613
|View full text |Cite
|
Sign up to set email alerts
|

Activity- vs. structural-oriented treatment approach for frozen shoulder: a randomized controlled trial

Abstract: Therapy based on performing activities seems to be more effective for pain reduction and the ability to perform daily life activities than conventional treatment methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 25 publications
1
29
0
2
Order By: Relevance
“…The majority of included trials (11 of 14) measured pain intensity only at rest 15,36,[38][39][40][41][42][43][44][45]48 . One study measured the intensity of pain during movement (39), and one study evaluated pain intensity on movement and at rest 36 .…”
Section: Pain Intensitymentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of included trials (11 of 14) measured pain intensity only at rest 15,36,[38][39][40][41][42][43][44][45]48 . One study measured the intensity of pain during movement (39), and one study evaluated pain intensity on movement and at rest 36 .…”
Section: Pain Intensitymentioning
confidence: 99%
“…Five studies evaluated the intensity of pain through the visual analog scale (VAS) 15,39,[41][42][43] and other four studies used the numerical rating scale (NRS) 36,[38][39][40] . One study evaluated pain through the McGill Pain Questionnaire 48 . In study 49 VAS was used to evaluate pain intensity associated with nociceptive flexion reflex test 49 .…”
Section: Pain Intensitymentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of physiotherapy measures should be optimal preservation of any mobility that is still present. Horst et al showed improved efficacy of activity-oriented treatment programmes compared with conventional structure-oriented approaches [18]. To achieve this, physiotherapy courses in the inpatient setting were proposed to improve the results of the subsequent independent exercises at home, thereby reducing the number of further visits to the hospital [19].…”
Section: Physiotherapymentioning
confidence: 99%
“…The right physiopathologic mechanism is not yet well-understood, but it is reported to be a chronic inflammatory process of synovium and soft tissue followed by a fibrotic picture similar to E. CavallEri, a. SErvadio, a. BErardi, M. Tofani, G. GalEoTo Dupuytren's disease, due to the rise of collagen formation, myofibroblasts and fibroplasias (10); some arthroscopic and histologic studies have shown that the condition is caused by a glenohumeral capsule contracture, particularly of the coracohumeral ligament within the rotator interval (9). Another theory tells that if the immobilization due to injury and pain is kept up longer than necessary, it may lead to learned non-use, loss of cortical representation and then stiffness and pain (11). Early diagnosis is not easy: the first symptom is the onset of a nocturnal and daily pain causing restriction in function and daily activities (1)(2)(3)5); there is a loss of both passive and active movements, particularly a loss of more than 30° in passive external rotation (2); there is weakness of supraspinatus muscle and long head biceps lack of flexibility which cause limitation in abduction (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%